An Islamic multimedia learning application of menstruation for adolescent girls / Nur Irham Atikah Mohd Rafee @ Sukiman and Aznoora Osman - Mohd Rafee @ Sukiman, Nur Irham Atikah; Osman, Aznoora (College of Computing, Informatics and Media, UiTM Perlis, 2023)
Currently in Malaysia, adolescent girls learn about menstruation from the internet and school textbooks such as in Islamic Education and Physical Education and Health subjects. Although they are taught about menstruation and hygiene care, the textbooks contain so little information about menstruation from an Islamic perspective. In an effort to raise awareness about hygiene care of menstruation for Muslim adolescent girls, there should be more engaging digital learning materials. The Islamic multimedia learning application, entitled ‘Lily’ was created as a prototype for educating early adolescent girls on hygiene care and prohibitions during menstruation based on Islamic teaching. The user experience test was conducted over a period of two weeks with 26 girls where they were required to explore Lily thoroughly, then they were administered with the User Experience Questionnaire. The UEQ consisted of 26-items to measure their feedback regarding their experience after using the application. It was discovered that Lily received a positive mean score in all six major areas of user experience which are Attractiveness, Perspicuity, Efficiency, Dependability, Stimulation and Novelty.